Experience of The Active Tiktok User Community In Shopping Via Tiktok Shop - Novitasari,; Ahmad Nur Kholis,; Luhjingga Panasari Urbaningrum,; Ali Rokhman, (Jurnal Sosial Humaniora, 2025)
This research aims to analyze the experience of active tiktok users in shopping through the tiktok shop in Banyumas Regency. The Tiktok application is one of the social media platforms that is very popular with the public. The reason is that the tiktok application is able to provide shopping features, making it easier for tiktok users to buy products directly. The research method used is descriptive quantitative. Research data was collected through questionnaires distributed using google form. The questionnaire was distributed to active tiktok user communities in Banyumas Regency. The research was analyzed using the rapidminer application. The results of the research show that people who use tiktok shop in Banyumas Regency feel satisfaction in their shopping experience and most respond to satisfaction by selecting the “Agree” of “Strongly Agree” options. The results of the research show that people who use tiktok shop in Banyumas Regency feel satisfaction in their shopping experience and most respond to satisfaction by selecting the “Agree” or “Strongly Agree” and “Neutral” options. The characteristics of individuals who choose the “Agree” or “Strongly Agree” and “Neutral” options are based on gender, occupation, age, and experience in shopping on Tiktok. Female respondents have a relatively high sense of satisfaction. Meanwhile, male respondents have a more neutal attitude due to individual chatacteristics that are less interested in the features in the tiktok shop. Therefore, tiktok needs to improve its features and collaborate with various parties such as the government, police, and bank. Also, the existence of gender preferences increases satisfaction for active tiktok users in their online shopping experience.